Economic and environmental effectiveness of implementing circular economy principles in Uzbekistan - Rustamova Sarvinoz Azizbek kyzy (THE INNOVATION ECONOMY, 2026)
This study examines the economic savings and environmental benefits of implementing circular economy principles in Uzbekistan. Based on field observations across household, industrial, and agricultural sectors, as well as official statistical data, the research assesses the potential of circular approaches to reduce waste, conserve natural resources, and generate employment. Key barriers—including financial constraints, an underdeveloped regulatory framework, and insufficient recycling infrastructure—are also identified. Findings underscore the need for a systematic, nationwide strategy to scale up circular economy practices.